Interaction of calcitonin gene related peptide (CGRP) and substance P (SP) in human skin. (October 2016) - Schlereth, Tanja; Schukraft, Jonas; Krämer-Best, Heidrun H.; Geber, Christian; Ackermann, Tatiana; Birklein, Frank
Abstract: Calcitonin gene related peptide (CGRP) and substance P (SP) are neuropeptides that are simultaneously released from nociceptive C-fibers. CGRP is a potent vasodilator, inducing a long-lasting increase in superficial skin blood flow, whereas SP induces only a brief vasodilation but a significant plasma extravasation. CGRP and SP may play important roles in the pathophysiology of various pain states but little is known about their interaction. Different concentrations of SP (ranging from 10 − 5 M to 10 − 9 M) were applied to the volar forearm of 24 healthy subjects via dermal microdialysis. SP was applied either alone or in combination with CGRP10 − 9 M and CGRP 10 − 6 M. As expected, SP induced a transient increase in skin blood flow that decayed shortly after application. This transient blood flow peak was blunted with co-application of CGRP 10 − 9 M and inhibited with co-application of CGRP10 − 6 M. SP alone induced plasma protein extravasation (PPE). However, when CGRP10 − 6 M was added, the PPE significantly increased. Our results demonstrate a complex interaction of the neuropeptides CGRP and SP. CGRP10 − 6 M prevented SP-induced early vasodilation but augmented SP-induced PPE. These interactions might explain why vascular symptoms in chronic pain can differ strikingly between individuals. Highlights: SP induced short-lasting vasodilatation, which was reduced by co-application of CGRP. Co-application of CGRP induced a long-lasting vasodilatation dose-dependently. SP induced plasma protein extravasation (PPE), which was enhanced by CGRP. Interaction of CGRP and SP is complex: CGRP inhibits SP-induced blood flow, but increases PPE.